2000
DOI: 10.1074/jbc.m909440199
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Host Cell Phosphatidylinositol 3-Kinases byTrypanosoma cruzi Infection

Abstract: Trypanosoma cruzi, the causative agent of Chagas' disease in humans, is an intracellular protozoan parasite with the ability to invade a wide variety of mammalian cells by a unique and remarkable process in cell biology that is poorly understood. Here we present evidence suggesting a role for the host phosphatidylinositol (PI) 3-kinases during T. cruzi invasion. The PI 3-kinase inhibitor wortmannin marked inhibited T. cruzi infection when macrophages were pretreated for 20 min at 37°C before inoculation. Infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
5
46
0
1
Order By: Relevance
“…Thus, TS promotes Schwann-cell survival by activating a signal-transduction cascade used by authentic cell survival-promoting mammalian neurotrophic growth factors (31). Although T. cruzi infection of macrophages triggers PI3K activation (32), it remains to be determined whether TS is the active T. cruzi-activating factor in those cell types. (A) GFP-and GFP͞AktKI-transfected Schwann cells were maintained in 0.1% FCS for 48 hr without tetracycline (to induce GFP and AktKI expression) in the absence (GFP and AktKI, respectively) or presence (GFP͞cTS and AktKI͞cTS) of 500 ng͞ml of cTS for 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TS promotes Schwann-cell survival by activating a signal-transduction cascade used by authentic cell survival-promoting mammalian neurotrophic growth factors (31). Although T. cruzi infection of macrophages triggers PI3K activation (32), it remains to be determined whether TS is the active T. cruzi-activating factor in those cell types. (A) GFP-and GFP͞AktKI-transfected Schwann cells were maintained in 0.1% FCS for 48 hr without tetracycline (to induce GFP and AktKI expression) in the absence (GFP and AktKI, respectively) or presence (GFP͞cTS and AktKI͞cTS) of 500 ng͞ml of cTS for 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning in this context that the invasion of host cells by MTs of the CL strain depends on tyrosine phosphorylation and the IP � -dependent (1,4,5-inositol-triphosphate) release of calcium from endoplasmic reticulum (ER) stores, whereas MTs of the G strain engage adenylate cyclase and cause calcium to be mobilised from acidocalcisomes (Neira et al 2002). No comparative data between both strains is evaluable for TCTs, but inhibitors of class I and class III PI�-K activities block the entry of the parasite into macrophages, suggesting the involvement of different isoforms of this kinase (Todorov et al 2000). On the other hand, it seems that calcium mobilisation from acidocalcisomes, but not from the ER, is important for cellular invasion by extracellular amastigotes of either the G or CL strains (Mor-Mortara et al 2005, Fernandes et al 200�, Scharfstein et al 200�, 2008, Scharfstein & Lima 2008.…”
Section: Signalling Mechanisms and Molecules Involved In T Cruzi Invmentioning
confidence: 99%
“…�dditional evidence suggests the participation of components of the early endocytic trafficking pathway, such as dynamin and Rab5, and indicates that the lysosomal process might be both more elaborate and downstream of earlier events (Wilkowsky et al 2002). Previous studies (Todorov et al 2000, Wilkowsky et al 2001) have used a quantitative approach to iden-2001) have used a quantitative approach to idenhave used a quantitative approach to identify the role of phosphatidyl-inositol �-kinase (PI�-K) (Woolsey et al 200�) in the lysosomal pathway and ob- Woolsey et al 200�) in the lysosomal pathway and obin the lysosomal pathway and observed that this key cellular component is involved in a lysosome-independent T. cruzi internalisation pathway utilised by TCTs. Trypomastigotes that use this route mobilise phosphorylated inositides during the formation of the PV.…”
Section: Biology Of T Cruzi-host Cell Invasionmentioning
confidence: 99%
“…During cell invasion, phosphoinositol 3-kinases (PI 3Ks) are also activated; inhibition of these kinases blocks the parasite's internalization (Todorov, et al 2000;Yoshida, 2006). The regulatory sub-unit of PI-3K, p85, co-localizes with actin filaments at the sites of parasite entry into macrophages (Vieira, et al 2002).…”
Section: Signal Transduction Pathway Activation In the Hostmentioning
confidence: 99%